Birth Weight and Cardiorespiratory Fitness Among Young Men Born at Term: The Role of Genetic and Environmental Factors. Issue 3 (4th February 2020) - Ahlqvist, Viktor H.; Persson, Margareta; Ortega, Francisco B.; Tynelius, Per; Magnusson, Cecilia; Berglind, Daniel
Abstract : Background: Preterm delivery and low birth weight are prospectively associated with low cardiorespiratory fitness (CRF). However, whether birth weight, within the at‐term range, is associated with later CRF is largely unknown. Thus, the aim of the current study was to examine this issue and whether such association, if any, is explained by shared and/or nonshared familial factors. Methods and Results: We conducted a prospective cohort study, including 286 761 young male adults and a subset of 52 544 siblings born at‐term. Objectively measured data were retrieved from total population registers. CRF was tested at conscription and defined as the maximal load obtained on a cycle ergometer. We used linear and nonlinear and fixed‐effects regression analyses to explore associations between birth weight and CRF. Higher birth weight, within the at‐term range, was strongly associated with increasing CRF in a linear fashion. Each SD increase in birth weight was associated with an increase of 7.9 (95% CI, 7.8–8.1) and 6.6 (95% CI; 5.9–7.3) Wmax in the total and sibling cohorts, respectively. The association did not vary with young adulthood body mass index. Conclusions: Birth weight is strongly associated with increasing CRF in young adulthood among men born at‐term, across all categories of body mass index. This association appears to be mainly driven by factors that are not shared between siblings. Hence, CRF may to some extent be determined already in utero. Prevention of low birth weight, also within the at‐term‐range, can be a feasible mean of increasing adult CRF and health.